2002
DOI: 10.1134/1.1475721
|View full text |Cite
|
Sign up to set email alerts
|

Critical current in SFIFS junctions

Abstract: Quantitative theory of the Josephson effect in SFIFS junctions (S denotes bulk superconductor, F - metallic ferromagnet, I - insulating barrier) is presented in the dirty limit. Fully self-consistent numerical procedure is employed to solve the Usadel equations at arbitrary values of the F-layers thicknesses, magnetizations, and interface parameters. In the case of antiparallel ferromagnets' magnetizations the effect of the critical current enhancement by the exchange field is observed, while in the case of pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
122
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(134 citation statements)
references
References 8 publications
12
122
0
Order By: Relevance
“…We will show that in the former case the condition is equivalent to the one of Ref. 21 , while in the latter case the new condition is found. The calculation will be performed in the zero-temperature regime by varying the interface resistances as well as the resistance, the exchange field and the Thouless energy of the DF layer.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…We will show that in the former case the condition is equivalent to the one of Ref. 21 , while in the latter case the new condition is found. The calculation will be performed in the zero-temperature regime by varying the interface resistances as well as the resistance, the exchange field and the Thouless energy of the DF layer.…”
mentioning
confidence: 88%
“…Experimentally DOS in F/S bilayers was measured by Kontos et al who found a broad DOS peak around zero energy when the π-phase shift occurs 22 . In diffusive ferromagnet/superconductor (DF/S) junctions the zeroenergy DOS may have a sharp peak 21 . However the conditions for the appearance of such anomaly have not been studied systematically so far.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,20,21,22 However, a theory of the phase-coherent electronic transport in mesoscopic structures should be based on the solutions of Gor'kov or Bogoliubov-de Gennes (BdG) equations. The coherence effects have been studied recently for double-barrier SINIS junctions containing an interlayer of a clean nonmagnetic metal (N) with insulating interfaces (I), 23 and for FISIF junctions.…”
mentioning
confidence: 99%
“…The various effects on the superconducting critical temperature, field and current density, (T C , H C and J C ), of the parallel and anti-parallel configurations of the F layers is of great interest. Various theoretical predictions have been made for J C enhancement in the case of S/F/X/F/S Josephson junctions, when the F layers have their moments switched from parallel to antiparallel, with large effects for X = insulator (I), [9,10,11], more weakly in the case of X = normal (dirty) metal (N) [12]. Spin torque on the F layers due to the Josephson current has been predicted for X = N [13].…”
Section: Introductionmentioning
confidence: 99%